DIGITALIZATION OF REGIONAL ECONOMIC SYSTEMS AS AN ANTI-CORRUPTION FACTOR AND ENSURING ECONOMIC SECURITY OF THE STATE - IVANOVA, NATALIIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article is devoted to the study of the impact of the phenomenon of "corruption" in state authorities on ensuring the economic security of Ukraine. The issue of digitization of regional economic systems and the importance of using digital tools in the field of preventing and overcoming corruption risks are considered. The article analyzes the approaches to the definition of "corruption", gives the results of the assessment of the economic and anti-corruption effect of the introduction of electronic governance. The author substantiates the need to strengthen the institutional basis for overcoming corruption risks, which involves the development of three levels: anti-corruption legislation, anti-corruption infrastructure and digitization of anti-corruption activities. Taking into account the strategy of decentralization of power and the transfer of many decisions to the regional level, the digitalization of regional economic systems acquires special importance, and the economic and anti-corruption effects are formed in the triad of "citizens-business-state", which are manifested in the form of saving time, costs and the emergence of new opportunities development and self-realization. It was found that users may prefer the traditional offline procedure due to the lack of access to the Internet, the desire to receive prompt feedback (for example, regarding the completeness of the package of documents and their correctness), as well as if they want to resort to corrupt actions (for example, to speed up receiving a service). Among the factors external to the consumer, one can note the insufficient adaptability of services for digitalization (not all services can be provided qualitatively without personal contact); legal and administrative imperfection of the services themselves, which are translated into online format; the presence in the chain of officials who have the right to make a decision; and the presence of deficiencies in the functioning of the e-government infrastructure. Recommendations for increasing the effectiveness of the anti-corruption policy have been developed, based on the identified factors of the potential refusal of consumers of public services from their digitalization.
Keywords: corruption; economic security; regional economic system; digitalization; anti-corruption legislation; anti-corruption infrastructure; digitalization of anti-corruption activities